Treatment of Atrophic Mandibular Fractures with the Pencilboneplate: Report of 2 Cases - Oliveira, Henrique do Couto de [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Gabrielli, Mario Francisco Real [UNESP] (Springer Nature, 2012)
The incidence of fractures of the atrophic edentulous mandible is still low, even with the increasing life expectancy. The reduced blood supply of the sclerotic bone, the diminished contact area between bone fragments and the patient’s systemic condition makes the treatment of those fractures a challenge for any professional. Treatment of atrophic mandibular fractures by means of miniplate osteosynthesis has not been the preferred method of fixa- tion by many authors. Yet, many surgeons have applied this type of fixation for the atrophied jaw sections. This paper reports 2 cases of fractured atrophic mandibles treated with the pencilboneplate, a monocortical 2.0 mm titanium, 8 or 10-hole hardware with reinforcement on its middle portion, highlighting important considerations of its use. The pencilboneplate appears to be a valuable option for the treatment of atrophic mandibular fractures, espe- cially by an intra-oral approach, and warrants further bio- mechanical and clinical studies.
Keywords: Fracture; Mandible; Elderly; Osteosynthesis